Development of Interactive Learning Multimedia by Applying Contextual Teaching and Learning for Basic Graphic Design Subjects - Ayuriyanti, Siswi Dwi; Surjono, Herman Dwi (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2023)
The objectives of this study were to 1) create interactive learning multimedia materials by incorporating contextual teaching and learning to aid students in understanding graphic design topics for class X, 2) examine the viability of interactive learning multimedia by incorporating contextual teaching and learning to fundamental design subjects, and 3) assess the efficacy of using interactive learning multimedia by incorporating contextual teaching and learning. The three stages of this research's development-planning, design, and development are based on the Alessi and Trollip model. A total of 36 students from class X Multimedia 2 at SMK N 2 Sewon served as the research participants, while X Multimedia 1 served as the control group. gathering information through observation, questionnaires, learning product assessments, and learning accomplishment tests the findings revealed that: 1) Multimedia interactive learning materials for the foundational subject of graphic design in class X multimedia semester 2 at SMK N 2 Sewon were prepared. 2) Students (87.77%;